Misperceptions and Fake News during the Covid-19 Pandemic - Kerim Peren Arin; Juan A. Lacomba; Francisco Lagos; Deni Mazrekaj; Marcel Thum (Center for Economic Studies and Ifo Institute (CESifo), 2021)
By conducting large-scale surveys in four European countries, we investigate the determinants of right- and left-wing misperceptions as well as fake news exposure and sharing. We also shed light on how the COVID-19 pandemic influenced both misperceptions and fake news. Our results indicate that people substantially overestimate the share of immigrants, Muslims, people under the poverty line, and the income share of the richest. Female, lower-income, and lower-educated respondents have higher misperceptions, whereas the higher-educated, male, married, right-wing and, younger respondents share fake news more often, both intentionally and unintentionally. The COVID-19 pandemic increased fake news sharing and amplified right-wing misperceptions.
Keywords: D70; H11; H12; H41; I18; 330; Covid-19; lockdown; misperceptions; fake news